Ionizing radiation causes increased tau phosphorylation in primary neurons. (16th June 2014) - Li, Li; Wang, Wenzhang; Welford, Scott; Zhang, Teng; Wang, Xinglong; Zhu, Xiongwei
Abstract Radiotherapy is the major treatment modality for primary and metastatic brain tumors which involves the exposure of brain to ionizing radiation. Ionizing radiation can induce various detrimental pathophysiological effects in the adult brain, and Alzheimer's disease and related neurodegenerative disorders are considered to be late effects of radiation. In this study, we investigated whether ionizing radiation causes changes in tau phosphorylation in cultured primary neurons similar to that in Alzheimer's disease. We demonstrated that exposure to 0.5 or 2 Gy γ rays causes increased phosphorylation of tau protein at several phosphorylation sites in a time‐ and dose‐dependent manner. Consistently, we also found ionizing radiation causes increased activation of GSK3β, c‐Jun N‐terminal kinase and extracellular signal‐regulated kinase before radiation‐induced increase in tau phosphorylation. Specific inhibitors of these kinases almost fully blocked radiation‐induced tau phosphorylation. Our studies further revealed that oxidative stress plays an important role in ionizing radiation‐induced tau phosphorylation, likely through the activation of c‐Jun N‐terminal kinase and extracellular signal‐regulated kinase, but not GSK3β. Overall, our studies suggest that ionizing radiation may cause increased risk for development of Alzheimer's disease by promoting abnormal tau phosphorylation. <boxed-text content-type="graphic" id="jnc12769-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text> Alzheimer disease is considered as a significant radiation late effect. In this study, we investigated whether ionizing radiation causes changes in tau phosphorylation and found that γ rays cause increased tau phosphorylation at multiple sites in a dose and time‐dependent manner in primary neurons which are mediated by oxidative stress‐dependent activation of JNK and ERK. Oxidative stress‐independent activation of GSK3β is also involved. Overall, our studies suggest that ionizing radiation may cause increased risk for Alzheimer disease development by promoting abnormal tau phosphorylation.